(untitled) - Hallows, Richarch (Boston, MA)
This book is two level preparation course for candidates studing for the international english language testing system examination.IELTS-type tasks and practice activities provide students with the essential skills they need for exam success.
Keywords: International English Language Testing System,English language,English language,Anh ngữ,Anh ngữ; Textbooks for foreign speakers,Examinations,Study guides,Giáo trình dành cho người nước ngoài,Kỳ thi,Sách hướng dẫn